The Effect of Work Stress on Employee Performance at Pt Isuzu Astra Motor Indonesia - Mardianto, David; Kristanto, Yudi; Taryanto, Taryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to examine the significant effect of Job Stress on employee performance of PT Isuzu Astra Motor Indonesia both partially and simultaneously. The method used in this research is quantitative analysis method. Where the subjects in this study were employees of PT Isuzu Astra Motor Indonesia totalling 40 samples. The primary data collection technique through questionnaires and secondary data collection through library research. While the data analysis methods used are Validity Test, Reliability Test, Data Analysis Prerequisite Test, Partial Hypothesis Test (t test), and Coefficient of Determination (R2). The results showed, based on the calculation results obtained a correlation coefficient of r = 0,702 and a coefficient of determination of R = r2 = 0.493. Significance testing of the correlation obtained tcount (6.078) > t table (2.021) at ɑ = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between Job Stress and Employee Performance can be accepted. This means that the higher a person's Job Stress will be followed by a decrease in employee performance. Meanwhile, the coefficient of determination of 0.493 shows that 49,3% of variations in employee performance can be explained by variations in Work Stress, the remaining 50,7% is determined by other factors outside of Work Stress